2021
DOI: 10.1200/jco.2021.39.15_suppl.e16029
|View full text |Cite
|
Sign up to set email alerts
|

Phase-II study of toripalimab combined with neoadjuvant chemotherapy for the treatment of resectable esophageal squamous cell carcinoma.

Abstract: e16029 Background: Compared with neoadjuvant chemotherapy alone,Neoadjuvant radiochemotherapy can significantly increase pCR rate in esophageal squamous cell carcinoma and improve patient overall survival. However, the addition of radiotherapy increases the risk of adverse reactions and surgery. Neoadjuvant radiochemotherapy is currently used in < 5% of Chinese patients.The purpose of this phase II study is to assess the efficacy and safety of toripalimab combined with paclitaxel and cisplatin as neoadjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The geographic distribution of included studies is shown in eFigure 1 in the Supplement. non-RCTs, and 25 of them were single-group 21,22,[24][25][26][27]30,31,[33][34][35][36][37][39][40][41][42][43][44][45][46][47] and 2 were dual-group trials. 28,29 Twenty-three trials 21,23,24,[27][28][29][31][32][33][34][35][36][37][38][39][42][43][44]46,47 enrolled patients with ESCC and applied anti-PD-1 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The geographic distribution of included studies is shown in eFigure 1 in the Supplement. non-RCTs, and 25 of them were single-group 21,22,[24][25][26][27]30,31,[33][34][35][36][37][39][40][41][42][43][44][45][46][47] and 2 were dual-group trials. 28,29 Twenty-three trials 21,23,24,[27][28][29][31][32][33][34][35][36][37][38][39][42][43][44]46,47 enrolled patients with ESCC and applied anti-PD-1 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…non-RCTs, and 25 of them were single-group 21,22,[24][25][26][27]30,31,[33][34][35][36][37][39][40][41][42][43][44][45][46][47] and 2 were dual-group trials. 28,29 Twenty-three trials 21,23,24,[27][28][29][31][32][33][34][35][36][37][38][39][42][43][44]46,47 enrolled patients with ESCC and applied anti-PD-1 antibody. Four trials 22,26,30,45 enrolled patients with EAC, of which 2 used anti-PD-1 antibody 30,45 and 2 applied anti-PD-L1 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a phase II study (ChiCTR1900025318), 23 subjects with resectable ESCC were included and given toripalimab combined with paclitaxel and cisplatin as neoadjuvant treatment. Among the evaluable patients, 33.3% (6/18) achieved pCR ( 59 ). The combination regime also showed a controllable safety profile, and grade 3–4 treatment-related adverse events (TRAEs) were reported in two patients.…”
Section: Efficacy Of Toripalimab In Tumorsmentioning
confidence: 99%